2022
DOI: 10.3390/jpm12071090
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Concept of Obstetric Violence: Scoping Review Protocol

Abstract: (1) Background: Obstetric violence has been highlighted in the political and social agenda of several countries. Efforts have been made to create policies to humanize obstetric care, guarantee the rights of pregnant women and respond to this form of violence. The lack of consensus on the appropriate terminology to name and define the behaviours that constitute obstetric violence, hinders this process. (2) Objective: To analyse the concept of obstetric violence related to assistance to women during labor. (3) M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
3
0
7
Order By: Relevance
“…It was found that women that presented a birth plan that was not observed perceived more OV, with statistically significant differences and a considerable effect size. This might be due to the fact that those women had more information on the delivery and postpartum processes and were, thus, able to identify OV-related situations or procedures, especially those considered invisible practices [ 1 , 6 , 31 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that women that presented a birth plan that was not observed perceived more OV, with statistically significant differences and a considerable effect size. This might be due to the fact that those women had more information on the delivery and postpartum processes and were, thus, able to identify OV-related situations or procedures, especially those considered invisible practices [ 1 , 6 , 31 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the differences in OV prevalence must take into account the complexity of the construct [ 2 , 4 , 31 ] which, as mentioned, includes several attitudes and practices deeply influenced by social or cultural aspects as well as by medical factors [ 6 , 7 ]. Certain practices considered as OV may be not perceived as such by women or health professionals in certain contexts, which consequently influences the reported rates [ 2 , 6 , 9 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…O processo de gestação, que culmina com o nascimento, provoca uma transformação significativa na vida da mulher que se torna mãe, sendo amplamente valorizado como um dos momentos mais emocionantes para uma família, não importando sua composição. O parto é uma vivência marcante, onde a mãe e o bebê necessitam do suporte das equipes de saúde e do apoio familiar, que visam garantir o bem-estar e atender às necessidades de cada um dos envolvidos (Ferrão, 2022).…”
Section: Introductionunclassified
“…A VO, está ligado não apenas ao trabalho dos profissionais de saúde, mas também a deficiências estruturais em clínicas, hospitais e no sistema de saúde na totalidade. Isto pode assumir muitas formas, desde intimidação ou agressão verbal até negligência no tratamento, recusa em fornecer cuidados médicos a mulheres grávidas ou bebês, falha em informar os pacientes sobre procedimentos ou seguir decisões (Ferrão, 2022). São frequentes os relatos de violência: negação da presença do acompanhante de escolha da mulher; falta de informação sobre os diferentes procedimentos realizados durante o atendimento; cesarianas desnecessárias; privação do direito à alimentação e passeios; exames vaginais rotineiros e repetitivos sem justificativa; uso frequente de ocitocina para acelerar o parto; episiotomia sem consentimento das mulheres; e a manobra de Kristeller.…”
Section: Introductionunclassified
See 1 more Smart Citation